Effectiveness menstrual hygiene knowledge using booklet and leaflet media for adolescent girl - Pramesti, Hasna Dian; Suherni, Suherni; Djanah, Nur (Jurnal Kesehatan Ibu dan Anak, 2019)
Menstrual hygiene management (MHM) is a problem for adolescent girl in low- and middle-income countries (LMICs). Poor MHM may increase a woman’s susceptibility to reproductive tract infections (RTI), bacterial vaginosis (BV) infection, and urinary tract infection (UTI). Adolescent girl with better knowledge of menstrual hygiene and safe practices can reduce their vulnerability to RTI, BV and UTI. Health education is one of the right methods to provide information to adolescent termine comprehension differences after getting menstrual hygiene education through booklets and leaflets for adolescent girl. This research was quasi experiment with pretest-posttest design with control group design. The data was taken on June 2019 in An-Nur Islamic Boarding School, Sewon, Bantul. The sample for each group was 35 girl students. The instruments used questionnaires. The data was analysed using paired t-test and independent t-test. The paired t-test result of the knowledge of both groups has significant enhancement knowledge in pretest-postrest scores for booklet group (Mean Difference = 14.09; p = 0.000) and for leaflet group (Mean Difference = 7.83; p = 0.000). Result of independent t-test showed that there was a significant difference in knowledge enhancement in adolescent girl's knowledge scores in the pre-test and post-test between the group of booklet media with the leaflet media (Mean Difference = 6.26; p = 0.000). The health education on menstrual hygiene through booklet media was more effective than leaflets in adolescent girls.